Reservation-based Dedicated Lane Method for Mixed Autonomous and Human-operated Vehicles at Intersections. Issue 1 (May 2021) - Huang, Xin; Lin, Peiqun
Abstract: This paper develops a reservation-based dedicated lane (RDL) mechanism for mixed autonomous and human-operated vehicles at intersections in connected vehicle environment. The RDL mechanism is proposed to coordinate hybrid transport at intersections under the condition of dedicated land, improve the capacity of intersections, reduce delay and the number of stops. The overall RDL architecture consists of two essential sub-modules: a connected and autonomous vehicles (CAVs) speed guidance application, a signal-control application for human-operated vehicles (HVs). Thus, the proposed RDL strategy enables HV/CAV/signal cooperation in a connected vehicle environment. A set-projection algorithm and a three-segment linear speed profile are employed to control the trajectories of the CAV. The performance of the proposed method is evaluated by simulating various traffic conditions on an actual urban network. The simulation evaluation results show that, compared with the traditional signal control method, the model can significantly reduce the travel delay. The simulation experiments indicate that the penetration rate of CAV reaches 30%-40%, and proposed method can achieve considerable results.